Fatigue After Aneurysmal Subarachnoid Hemorrhage: Clinical Characteristics and Associated Factors in Patients With Good Outcome - Western, Elin; Nordenmark, Tonje Haug; Sorteberg, Wilhelm; Karic, Tanja; Sorteberg, Angelika (Frontiers in Behavioral Neuroscience, 2021)
Fatigue after aneurysmal subarachnoid hemorrhage (post-aSAH fatigue) is a frequent, often long-lasting, but still poorly studied sequel. The aim of the present study was to characterize the nature of post-aSAH fatigue with an itemized analysis of the Fatigue Severity Scale and Mental Fatigue Scale. We further wanted to assess the association of fatigue with other commonly observed problems after aSAH: mood disorders, cognitive problems, health-related quality of life (HRQoL), weight gain and return to work (RTW). Ninety-six good outcome aSAH patients with fatigue completed questionnaires measuring fatigue, depression, anxiety and HRQoL. All patients underwent a physical and neurological examination. Cognitive functioning was assessed with a neuropsychological test battery. We also registered prior history of fatigue and mood disorders as well as occupational status and RTW. The patients experienced fatigue as being among their three most disabling symptoms and when characterizing their fatigue they emphasized the questionnaire items “low motivation”, “mental fatigue” and “sensitivity to stress”. Fatigue due to exercise was their least bothersome aspect of fatigue and weight gain was associated with depressive symptoms rather than the severity of fatigue. Although there was a strong association between fatigue and mood disorders, especially for depression, the overlap was incomplete. Post-aSAH fatigue related to reduced HRQoL. RTW was remarkably low with only 10.3% of patients returning to their previous workload. Fatigue was not related to cognitive functioning or neurological status. Although there was a strong association between fatigue and depression, the incomplete overlap supports the notion of these two being distinct constructs. Moreover, post-aSAH fatigue can exist without significant neurological or cognitive impairments, but is related to reduced HRQoL and contributes to low rate of RTW.